Muscle Injuries Clinical Guide 3.0 (2015)
The aim of the following chapters is to outline the importance of muscle injuries in sports medicine, especially in football. Everybody is aware that muscle injuries, and particularly hamstring injuries are one of the most frequent injuries and due to these, a player will have long periods of time lost. For this reason, our medical staff decided to create the first muscle guide in 2009, to provide tools and explain our particular experience in managing muscle injuries. During the following years, we applied the guidelines in our guide, but day by day it made us learn new experiences that became the basis for the new guide which focuses on the hamstring injuries, but has a common framework which could be applied when managing other types of muscle injuries. Collecting data, we realised that in young football players, particularly in teenagers, the most common injury was a tear of the rectus femoris, whereas in professional football players it was the hamstring. This is the main reason why we decided to focus this second guide on describing hamstring injuries in depth. The second guide was written in collaboration with Aspetar Medical Staff and from now on we want to start the third guide taking into account our mutual knowledge based on clinical experiences and supported by scientific evidence. Going through the key changes in the second guide the most important are: